A high-intensity intermittent-based running programme allows triathletes to reduce weekly running distances without impairing muscular performance and body composition - Garcia-Pinillos, F.; Gonzalez-Fernandez, F. T.; Soto-Hermoso, V. M.; Latorre-Roman, P. A. (Isokinetics and Exercise Science, 2016)
BACKGROUND: Extensive evidence supports the benefits of high-intensity intermittent training (HIIT) for endurance athletes. Additionally, the importance of neuromuscular characteristics and body composition in determining running economy and, thereby running performance, have been widely documented. Previous studies performing HIIT interventions have focused on single sports, such as swimming, running or cycling, but not on multiple-event such as triathlon. AIM: This study aimed to determine the effect of a 5-week HIIT-based running programme on body composition and muscular performance parameters in triathletes. METHODS: Thirteen triathletes were matched into two groups, experimental group (EG) and control group (CG). The CG was asked to maintain their training routines, whilst the EG modified their running plans (HIIT-based) but maintained their swimming and cycling routines. Body composition, vertical jump, stretch-shortening cycle utilization (SSC) and sprint ability were performed before (pretest) and after (posttest) the intervention period. RESULTS: No significant differences between groups were found at pretest. At posttest, the EG obtained higher values in countermovement jump (p = 0.005, ES > 0.7) and SSC (p = 0.017, ES > 0.7), with lower times (p = 0.001, ES > 0.7) in sprint. Body composition parameters remained unchanged in both groups (p= 0.05, ES < 0.4). CONCLUSION: These preliminary results show that a HIIT-based running plan may induce improvements superior to the plan performed by the CG, in jumping, sprinting ability and SSC, without impairing body composition parameters. Thus, this study highlights the effectiveness of HIIT-based training programme for improving explosive muscular power and the rebound capabilities of the athletes. ABSTRACT FROM AUTHOR